ANALISIS IMPLEMENTASI GOOD CORPORATE GOVERNANCE DAN PENERAPAN PSAK 109 TENTANG AKUNTANSI ZAKAT PADA LEMBAGA AMIL ZAKAT DOMPET DHUAFA CABANG SULAWESI SELATAN - H. Mustafa Hasbar (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
This study aims to: (1) analyze the implementation of Good Corporate Governance at the Institute Amil Zakat Dompet Dhuafa South Sulawesi branch; (2) describe the application of SFAS 109 on accounting for zakat Amil Zakat Institution Dompet Dhuafa Branch South Sulawesi This study used a qualitative approach to the type of research is a field research. This study was conducted from November 2015 to January 2016. Data were analyzed using descriptive analysis The results of this study indicate that: (1) Implementation of the Principles of Good Corporate Governance (GCG) has applied to the Institute Amil Zakat Dompet Dhuafa Branch South Sulawesi: (2) Statement of Financial Accounting Standards (SFAS) 109 has been applied both in Amil Zakat wallets Dhuafa Branch South Sulawesi